Tawhidic Paradigm Index as a Measuring Tool of Tawhidic Practice: A Research in Universiti Tun Hussein Onn Malaysia - Mohd Khalid, Halimi; Azman Hasan; Abdullah Sulaiman; Shakila Ahmad; Hemmy Abd. Jalal (Advances in Humanities and Contemporary Studies, 2022)
The paradigm of Tauhid is a framework of world view that Allah SWT as al Khaliq and man as al-makhluk. This world view is based on the integrated relationship between God and man, man with man and man with nature. This relationship is based on three main cores, namely knowledge, faith and deeds through the appreciation of faith, sharia and morals to achieve happiness in this world and the hereafter. In general, this is a holistic and integrated concept in shaping the personal character of a noble human being. However, it is seen as too abstract to make it impossible to measure. In general, this is a holistic and integrated concept in shaping the personal character of a noble human being. However, it is seen as too abstract to make it impossible to measure and prove scientifically. Therefore, the Paradigm of Tauhid remains a slogan that is fought for but difficult to achieve.However, this research managed to prove that the tawhidic paradigm is in fact an abstract thinking framework that covers both theoretical and practical aspects. The reason for choosing this concept is because it is seen as packed in a holistic manner that includes the aim of humans’ life that is to succeed in the world and hereafter. This writing intends to put forward a new innovation in the research of Tawhidic Paradigm that is; Tawhidic Paradigm Index (IPT). IPT is a measurement tool to designate the percentage or the value of Tawhidic practice in an organisation mainly a higher learning institution in a form of statistical value. The index is unique because it is rabbani, universal, flexible and measurable. The research employed an empirical method and used Exploratory Sequential Mixed Method approach with four-phased research. The findings of the research hoped to assist organisations that incline towards the concept in measuring the extent of tawhidic paradigm practice in their respective organisation.